2000
DOI: 10.1152/ajpgi.2000.278.1.g10
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of EGF is associated with the delay of ulcer healing by cigarette smoking

Abstract: Cigarette smoking is associated with peptic ulcer diseases. Smokers have lower levels of salivary epidermal growth factor (EGF) than nonsmokers. We investigated whether reduction of EGF is involved in the delay of gastric ulcer healing by cigarette smoking. Rats with acetic acid-induced ulcers were exposed to cigarette smoke (0, 2, or 4% vol/vol) 1 day after ulcer induction. EGF level was elevated 1 day after ulcer induction in salivary glands and serum, and 4 days after ulcer induction in the gastric mucosa. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
1
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 34 publications
0
42
1
2
Order By: Relevance
“…3B). To investigate whether rCRAMP influenced proliferation and angiogenesis by induction of EGF and/or vascular endothelial growth factor synthesis (Jones et al, 1999;Ma et al, 2000), we determined the protein levels of these factors in the gastric mucosa on day 4 after ulcer induction and found that their expression was not affected by the rCRAMP gene therapy (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3B). To investigate whether rCRAMP influenced proliferation and angiogenesis by induction of EGF and/or vascular endothelial growth factor synthesis (Jones et al, 1999;Ma et al, 2000), we determined the protein levels of these factors in the gastric mucosa on day 4 after ulcer induction and found that their expression was not affected by the rCRAMP gene therapy (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Gastric kissing ulcers were produced by luminal application of acetic acid. Animals were sacrificed on days 1, 4, 7, and 10 after ulcer induction, and the ulcer area was measured as described previously (Ma et al, 2000) by a person who was unaware of the type of treatment. After measuring the ulcerated area, a longitudinal section of stomach along the greater curvature, including the ulcer base and both sides of the ulcer margin, was fixed in 4% buffered formalin for 24 h at 4°C for histologic study.…”
Section: Methodsmentioning
confidence: 99%
“…Smoking has also been shown to reduce levels of various growth factors (31). It is thus likely that both cigarette smoking and chronic hypoxia decreased mucosal integrity and, as a result, mucosal injury was readily induced at lower dosages of prednisolone in CSE rats.…”
Section: Discussionmentioning
confidence: 99%
“…The detrimental effect of smoking is exhibited by inhibition of cell proliferation, mucus secretion and angiogenesis due to deficiency in EGF biosynthesis and its mRNA expression. The shortage of these factors is responsible for the delay in ulcer healing (104). Several spices and plant extracts such as Mexican tea herb and pilular adina herb, Chuanxiong spices, Capsaicin, Kuiyangping, Weitongning and Angelica sinensis interact with EGF synthesis and hence contribute to the gastroprotection.…”
Section: Herbs and Egfmentioning
confidence: 99%